Ultrasound-mediated rapamycin delivery for promoting osseointegration of 3D printed prosthetic interfaces via autophagy regulation in osteoporosis. (April 2022) - Li, Zuhao; Bai, Haotian; Wang, Zhonghan; Liu, Yuzhe; Ren, Ming; Wang, Xiangang; Gao, Weinan; Li, Qiuju; Wu, Minfei; Liu, He; Wang, Jincheng
Graphical abstract: Highlights: Bionic 3D printed porous titanium alloy has controllable pore size and porosity. Ultrasound-mediated rapamycin delivery restores the declined cellular activities of OP-BMSCs by upregulating the autophagy. This novel therapy effectively promote prosthetic interface osseointegration in osteoporosis. Abstract: Osteoporosis-derived bone marrow mesenchymal stem cells (OP-BMSCs) have impaired cell function, low osteogenic activity, and potential osteoclast inducibility, resulting in insufficient osseointegration and increased risk of catastrophic postoperative complications after arthroplasty. The low autophagy activity of OP-BMSCs contributed to poor osseointegration, which could be regulated by the classical autophagic activator, rapamycin. Hence, it is of great significance to regulate autophagy by rapamycin to promote osseointegration at the three-dimensional (3D) printed prosthetic interfaces under osteoporotic environment. In this study, 3D printed porous titanium alloy prosthetic interfaces with bionic pore size and porosity were prepared and implanted into the distal femur of osteoporosis rabbits. Subsequently, a transdermal drug delivery device was used to deliver rapamycin to the interfaces implantation sites. Ultrasound-mediated rapamycin delivery could restore the declined cellular activities (including cell viability, proliferation, migration, and osteogenesis), as well as inhibit potential osteoclast-inducing capacity and adipogenic differentiation by upregulating the autophagy level of OP-BMSCs. Moreover, percutaneous ultrasound-mediated rapamycin delivery significantly improved bone ingrowth and osseointegration of prosthetic interfaces in osteoporotic environment. To conclude, this novel therapy combining 3D printed bionic prosthesis and percutaneous ultrasound-mediated rapamycin delivery can effectively promote prosthetic interfaces osseointegration by regulating autophagy after arthroplasty for patients with osteoporosis.